Battery-energy-storage-based triple-active-bridge DC unified power quality conditioner for energy management and power quality enhancement of DC renewable sources. (December 2022) - Yang, Ruo Huan; Jin, Jian Xun; Mu, Shuai; Zhang, Ming Shun; Jiang, Shan; Chen, Xiao Yuan
Highlights: A triple-port-active-bridge-based DC unified power quality conditioner is proposed. Mathematical modeling of the proposed device is established. Transient response of DC wind turbine is analyzed. The proposed scheme is verified by experiment under voltage-current compensation. Simulation of DC wind turbine with the proposed protection is validated. Abstract: As the renewable-based DC power systems are expected to prevail in the near future, stochastic power and weakness of fault ride-through capability are essential issues in renewable-based DC power systems that urgently need to be addressed. This paper proposes a novel triple-port active bridge (TAB)-based DC unified power quality conditioner (DC-UPQC) for the performance enhancement of DC doubly-fed induction generator (DC-DFIG)-integrated DC power systems. The developed TAB-based DC-UPQC has the advantages of bidirectional voltage and current compensation ability, concise circuit structure, straightforward control system, and swift compensation response. The mathematical model, control strategy, and parameter selection of the TAB-based DC-UPQC are systematically analyzed. A scaled-down prototype for experimental verification is established to verify the theoretical analysis and the technical feasibility. Further, a 1.5-MW full-scale simulation of DC-DFIG is carried out to verify the effectiveness of the TAB-DC-UPQC in actual DC power systems. Simulation and experimental results show that the TAB-DC-UPQC has the integrated functions of smoothing output power of the DC-DFIG, limiting DC fault current and enhancing fault ride-through capability. Therefore, the TAB-DC-UPQC can be well expected to enhance the comprehensive energy management of the DC-DFIG wind energy conversion system and other renewable-based DC power systems.